Restless legs syndrome and nocturnal myoclonus: initial clinical manifestation of familial amyloid polyneuropathy. - Salvi, F (1990)
Restless legs syndrome was the first isolated clinical manifestation in four siblings of a family with familial amyloid polyneuropathy. Clinical and electrophysiological evidence of peripheral neuropathy appeared after a variable time interval. Polysomnography showed abnormal sleep patterns and nocturnal myoclonus in all patients. The restless legs syndrome responded favourably to clonazepam.